Family participatory clown therapy in venipuncture in hospitalized children: A non-randomized controlled trial. - Tianyu Chen; Qiying Chen; Zhenhua Lin; Jingfang Ye (PLoS ONE)
Objective To explore the effectiveness of family participatory clown therapy in venipuncture in hospitalized children. Methods We recruited 104 children aged 3 to 6 years for a non-randomized controlled trial from March to December 2022. All participants required peripheral venepuncture infusions for treatment. The children were assigned to either the control group (n = 52) or the experimental group (n = 52).Standard care was utilized in the control group. In the experimental group, two clown nurses and a parent provided family participatory clown therapy for 35-45 minutes per child before, during, and after venipuncture. We assessed children's pain (FLACC and W-B FPS), anxiety (VAS-A), medical fear (CFS), crying incidence, compliance, parental anxiety (S-AI), and parental satisfaction. Results At venipuncture, the FLACC score was lower in the experimental group (4.46±2.053) compared to the control group (5.96±2.441), the W-B FPS score was also lower in the experimental group (4.96±2.392) than in the control group (6.35±2.266), with a statistically significant difference (P<0.05).The children in the experimental group had lower levels of anxiety, medical fear, crying, and parental anxiety than the control group. In addition, child compliance and parent satisfaction were higher in the experimental group than in the control group, with statistically significant differences (P<0.05). Conclusion Family participatory clown therapy can reduce pain, anxiety, medical fear, and crying during venipuncture in children. It can also improve venipuncture compliance, reduce parental anxiety, and increase parental satisfaction.